Accelerated Pavement Testing Validation of a Pavement Response Model Using Three-Dimensional Finite Element Analysis Software: Two Case Studies. Issue 1 (January 2023) - Kaseer, Fawaz; Greene, James; Choubane, Bouzid
Accelerated pavement testing (APT) provides valuable information concerning the short- and long-term performance and life expectancy of pavement structures in a very short period as compared to full-scale field tests. Pavement modeling can produce early, reliable, and beneficial guidance that can be used to design and implement future APT experiments or extend the experimental results to similar materials and structures. Combining actual APT experimental data with well-calibrated models can provide complete and thorough investigations while saving agencies time and resources. The main objective of this study is to evaluate the effectiveness and accuracy of the 3D-Move Analysis Software (three-dimensional finite element software [3D FE]) in calculating pavement responses through a comparison with measured pavement responses and distresses from previous APT experiments using the Florida Department of Transportation heavy vehicle simulator (HVS). 3D-Move uses a continuum-based finite-layer approach to calculate pavement responses under various loading conditions. Results indicated that pavement responses, specifically longitudinal horizontal (tensile) strains at the bottom of the asphalt layer and transverse horizontal (tensile) strains at the surface of the asphalt layer, calculated by 3D FE are relatively similar to those measured in APT experiments. The calculated impact of the asphalt mixture properties, loading level, loading temperature, and the distance (offset) from the tire edge on pavement responses was consistent with those measured in HVS testing. Therefore, 3D FE analysis can be effectively used to compare the relative cracking performance of asphalt mixtures and aid in designing practical APT experiments and extending the results to similar asphalt mixtures and pavement structures.